Australian‐derived detrital zircons in the Permian‐Triassic Gympie terrane (eastern Australia): Evidence for an autochthonous origin. Issue 5 (7th May 2015) - Li, Pengfei; Rosenbaum, Gideon; Yang, Jin‐Hui; Hoy, Derek
Abstract The Tasmanides in eastern Australia record accretionary processes along the eastern Gondwana margin during the Phanerozoic. The Gympie terrane is the easternmost segment of the Tasmanides, but whether its origin was autochthonous or allochthonous is a matter of debate. We present U‐Pb ages of detrital zircons from Permian and Triassic sedimentary rocks of the Gympie terrane with the aim of tracing the source of the sediments and constraining their tectonic relationships with the Tasmanides. Our results show that the Permian stratigraphic units from the Gympie terrane mainly contain Carboniferous and Permian detrital zircons with dominant age peaks at 263 Ma, 300 Ma, 310 Ma, and 330 Ma. The provenance ages of the Triassic sedimentary units are similar ( 256 Ma, 295 Ma, and 328 Ma) with an additional younger age peak of 240 Ma. This pattern of provenance ages from the Gympie terrane is correlative to episodes of magmatism in the adjacent component of the Tasmanides (New England Orogen), indicating that the detrital zircons were dominantly derived from the Australian continent. Given the widespread input of detrital zircons from the Tasmanides, we think that the sedimentary sequence of the Gympie terrane was deposited along the margin of the eastern Australian continent, possibly in association with a Permo‐Triassic continental arc system. Our results do not show evidence for an exotic origin of the Gympie terrane, indicating that similarly to the vast majority of the Tasmanides, the Gympie terrane was genetically linked to the Australian continent.